2023
DOI: 10.56369/tsaes.4405
|View full text |Cite
|
Sign up to set email alerts
|

Positioning of White Oat Cultivars in Different Environments for High Grain Productivity in Organic System

Abstract: <p><strong>Background. </strong>White oat is a multifunctional species with significant benefits to human health, so the positioning of genotypes in the organic system is substantial to promote the expression of maximum productive potential. <strong>Objective.</strong> To select and identify the genotypes with greater stability and productive adaptability. <strong>Methodology.</strong> The study was carried out in 11 environments located in the countries of Brazil (sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…Multiple tools are genotype recommendations such as AMMI, GGE, REML/BLUP, and principal components. These are effective in recommending soybean genotypes , white oats (Savicki et al, 2023;Loro et al, 2022), and wheat (Segatto, et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Multiple tools are genotype recommendations such as AMMI, GGE, REML/BLUP, and principal components. These are effective in recommending soybean genotypes , white oats (Savicki et al, 2023;Loro et al, 2022), and wheat (Segatto, et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously with the development of genotypes tolerant to abiotic stress, the identification of environments with similar environmental conditions, known as megaenvironment assessment, improves the efficiency of genotype positioning (Katsenios et al, 2021). Studies have identified the presence of mega-environments in several cultures, as highlighted by Katsenios et al (2021), Szareski et al (2021) and Savicki et al (2023). This approach allows positioning genotypes within these mega-environments, which results in reduced costs in genetic breeding programs (Nardino et al, 2018) and provides favorable phenotypic responses.…”
Section: Introductionmentioning
confidence: 99%